Enhanced Recovery After Surgery in Older Adults Undergoing Colorectal Surgery: A Systematic Review and Meta-analysis of Randomized Controlled Trials. Issue 8 (10th May 2021) - Thillainadesan, Janani; Yumol, Minna F.; Suen, Michael; Hilmer, Sarah; Naganathan, Vasi
Abstract : Supplemental Digital Content is available in the text. Abstract : BACKGROUND: Enhanced recovery after surgery is increasingly applied in older adults undergoing colorectal surgery. OBJECTIVE: This systematic review and meta-analysis evaluated the impact of enhanced recovery protocols on clinical outcomes including hospital-acquired geriatric syndromes in older adults undergoing colorectal surgery. DATA SOURCES: This review was conducted according to PRISMA guidelines. Ovid MEDLINE, Embase, PsycINFO, Scopus, Cochrane Central Register of Controlled Trials, CINAHL, and trial registry databases were searched (January 1980 to April 2020). STUDY SELECTION: Two researchers independently screened all articles for eligibility. Randomized controlled trials evaluating enhanced recovery protocols in older adults undergoing colorectal surgery were included. INTERVENTION: The enhanced recovery protocol was utilized. MAIN OUTCOME MEASURES: Primary outcomes of interest were functional decline and delirium. Other outcomes studied were length of stay, complications, readmission, mortality, gut function, mobilization, pain, reoperation, quality of life, and psychological status. RESULTS: Seven randomized trials (n = 1277 participants) were included. In terms of hospital-acquired geriatric syndromes, functional decline was reported in 1 study with benefits reported in enhanced recovery after surgery participants, and meta-analyses showed reduced incidence of delirium (risk ratio, 0.45; 95% CI, 0.21–0.98). Meta-analyses also showed reduction in urinary tract infections (risk ratio, 0.53; 95% CI, 0.31–0.90), time to first flatus (standardized mean differences, –1.00; 95% CI, –1.98 to –0.02), time to first stool (standardized mean differences, –0.59; 95% CI, –0.76 to –0.42), time to mobilize postoperatively (standardized mean differences, –0.92; 95% CI, –1.27 to –0.58), time to achieve pain control (standardized mean differences, –0.59; 95% CI, –0.90 to –0.28), and hospital stay (mean differences, –2.20; 95% CI, –3.46 to –0.94). LIMITATIONS: The small number of randomized trials in older adults is a limitation of this study. CONCLUSIONS: Enhanced recovery protocols in older adults undergoing colorectal surgery appear to reduce the incidence of delirium and functional decline, 2 important hospital-acquired geriatric syndromes, as well as to improve other clinical outcomes. Future research should measure these geriatric syndromes and focus on high-risk older adults including those with frailty.